Crawling And Indexing Analysis System Based On Breadth First Search For Comparison Of Goods Value - Hendi Sama (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
This study aims to overcome the problems faced by users in conducting price searches for goods that are inconsistent due to the influence of various sources. Research activities were carried out over a period of 6 months. The method used in the implementation of this research is observation and analysis; and waterfall method. The system that was built started from the beginning through the data obtained, and the system design includes display design, diagrams of how the system works and how the user works, writing source code and implementing the system, the search method used in the system is a breadth first search. a technique that is widely adapted by the system. The result is a system that is built in accordance with the goals and benefits expected by the user and the implementation of the price comparison of goods in a web environment is ready to be implemented and has been tried by the users themselves. Information search algorithm techniques affects the information obtained, not all methods produce the same information; and the results obtained from the breadth first search technique affect the logic provided to the data parsing algorithm, so that the quality of information is also affected.